2018
DOI: 10.15406/sij.2018.02.00134
|View full text |Cite
|
Sign up to set email alerts
|

Increasing women’s representation in the Cameroon parliament: do numbers really matter?

Abstract: This paper examines the relationship between increasing the number of female legislators in Cameroon and it impact on gender-related policy, from a critical analysis of the participation of individual parliamentarians in influencing parliamentary proceedings and decisions within existing parliamentary structures. The study uses the concept of descriptive and substantive representation within the framework of the critical mass theory to investigate the extent to which an increase in the presence of women in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Some scholars have argued that an increase in the number of women in national parliaments does not translate to increased promotion of women's interests in bills passed, policies formulated, and necessary outcomes because in most cases members of parliaments are skewed towards party affiliations and interests. This is confirmed by Honorable Mary in an interview with Fokum and Fonjong (2018), where she states that though their number has increased in parliament, they cannot actually translate their numeric strength into articulating bills on the floor that would promote women's courses, especially because party interest/ideology is paramount. Secondly, the political structure is a semipresidential system in which bills are drawn from the executive and parliamentarians i.e.…”
Section: Results and Discussion Of Findingsmentioning
confidence: 98%
See 2 more Smart Citations
“…Some scholars have argued that an increase in the number of women in national parliaments does not translate to increased promotion of women's interests in bills passed, policies formulated, and necessary outcomes because in most cases members of parliaments are skewed towards party affiliations and interests. This is confirmed by Honorable Mary in an interview with Fokum and Fonjong (2018), where she states that though their number has increased in parliament, they cannot actually translate their numeric strength into articulating bills on the floor that would promote women's courses, especially because party interest/ideology is paramount. Secondly, the political structure is a semipresidential system in which bills are drawn from the executive and parliamentarians i.e.…”
Section: Results and Discussion Of Findingsmentioning
confidence: 98%
“…Again, Arhikiri et al, (2017) state that the physical presence of Ugandan women in decision-making structures signified a major breakthrough into a domain that was historically not theirs and concluded that the increased presence of Ugandan women enabled a shift in the public conversation while noting the efforts of women leaders, particularly women Members of Parliament (MPs), towards bringing women issues to public bare. Further, Fokum and Fonjong (2018) in their study of the Cameroon Parliament titled 'Increasing women's representation in the Cameroon parliament: do numbers really matter?' while using the parliamentary structures and the state (political regime) to analyze women's issues they interviewed 11 female MPs.…”
Section: Results and Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation